The Significance of Geolinguistics to the Ethnolinguistic Vitality of the Malays in Singapore: (Kepentingan Geolinguistik dalam Keberdayaan Etnolinguistik Melayu Singapura) (Jurnal Bahasa, 2014)
This research investigates the influence geolinguistics has on the ethnolinguistic vitality of Malays in Singapore using a sociological approach. Data were collected objectively based on sociological, economic, demographic and historical resources from censuses, research documents, and reports, as well as direct and indirect observations on the language and literary environment in Singapore. Data were analyzed following the theoretical framework of Giles et al. (1977)'s ethnolinguistic vitality in which status, demography, institutional support, and geography are identified as factors that affect the vitality of a group. The outcome of the analysis shows the vitality of the Malay language is in the range of low to medium, and there is a possibility of moving towards language deficit. However, there is strong support from informal organizations that contribute to the survival of Malay ethnic identity but this support is insufficient to safeguard the interests of the Malays together with the importance of the Malay language in Singapore. Geolinguistics is found to be the most important factor in ensuring that Malay remains relevant and continues to be used beyond its cultural sphere.Keywords: geolinguistics, ethnolinguistic vitality, linguapolitics, language maintenance, language shift, language policy, ethnicity.